2018
DOI: 10.1007/s10461-018-2247-6
|View full text |Cite
|
Sign up to set email alerts
|

How Do Gay Serodiscordant Couples in Sydney, Australia Negotiate Undetectable Viral Load for HIV Prevention?

Abstract: Many gay Australian serodiscordant couples are currently relying on an HIV-positive partner's undetectable viral load (UVL) to practice condomless sex. For these couples, preventing HIV is often considered a mutual responsibility, yet they lack a formally endorsed strategy that helps them navigate 'UVL for prevention' (UfP) as a couple. Drawing on interviews with 21 Australian gay men representing 15 serodiscordant couples, we explored 'the couple' within serodiscordant HIV prevention. In learning to rely on U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…Although a majority of HIV-negative partners were aware of the concepts underlying U = U, there were some who had not heard the message, and many did not believe it. Our findings are comparable to a study conducted in Zambia and South Africa that reported that people were largely unfamiliar with the prevention benefits of HIV treatment [14] and with studies done among gay men who expressed reluctance for condomless sex even after viral suppression [12,13]. Awareness and acceptance of the additional HIV prevention benefit of ART needs to go beyond targeting HIV-positive partners; including HIV-negative partners in U = U discussions could provide motivation for HIV-positive people to adhere to ART.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although a majority of HIV-negative partners were aware of the concepts underlying U = U, there were some who had not heard the message, and many did not believe it. Our findings are comparable to a study conducted in Zambia and South Africa that reported that people were largely unfamiliar with the prevention benefits of HIV treatment [14] and with studies done among gay men who expressed reluctance for condomless sex even after viral suppression [12,13]. Awareness and acceptance of the additional HIV prevention benefit of ART needs to go beyond targeting HIV-positive partners; including HIV-negative partners in U = U discussions could provide motivation for HIV-positive people to adhere to ART.…”
Section: Discussionsupporting
confidence: 81%
“…Studies conducted with gay and bisexual men have found low awareness of treatment as prevention . Additionally, HIV‐negative people report reluctance about engaging in condomless sex with HIV‐positive partners even after viral suppression unless they are on pre‐exposure prophylaxis (PrEP) . Notably, there is a paucity of data from heterosexual couples and their providers especially in developing countries about their understanding of the U = U concept .…”
Section: Introductionmentioning
confidence: 99%
“…As such, the promotion of couple‐level and relationally driven interventions hold the potential to benefit serodiscordant couples by counteracting stigma and improving engagement in HIV care and viral suppression (Conroy et al 2016a, 2016b, Philpot et al . 2018, Rodríguez de los Reyes and González 2017). Here our findings provide evidence that the serodiscordant couples represented and already embraced this type of couple‐level approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although all HIV‐positive study participants had their VL tested at baseline, it should be noted that Thai guidelines state that VL testing should commence at least six months after ART initiation , which may partially account for the lower levels of knowledge among HIV‐negative partners of their HIV‐positive partner's VL test results. If couples decide to rely on TasP within relationships, they should be encouraged to discuss VL results openly with each other to ensure that decisions are being made with the best possible information . This may particularly be the case in Thailand, where higher proportions of HIV‐negative partners did not know their partner's VL test results or had “not correct” perceptions.…”
Section: Discussionmentioning
confidence: 99%